2003
DOI: 10.1002/jbm.a.10024
|View full text |Cite
|
Sign up to set email alerts
|

The study of the sterilization effect of gamma ray irradiation of immobilized collagen polypropylene nonwoven fabric surfaces

Abstract: Exposure to gamma ray irradiation is a frequent, clean, and superior method used to prevent bacterial contamination of sterilized biomedical end products. However, the potential damage induced by gamma ray irradiation of collagen is of concern because of the decay of bioactivity, which correlates with considerable structural alterations. In this experiment, antenna-coupling microwave plasma was utilized to activate nonwoven polypropylene (PP) fabric, and then the sample was grafted to acrylic acid (AAc). Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Radiation within the gamma frequency range (> 3*10 19 Hz) penetrates packaging materials, and can be easily applied on a large scale at ambient temperatures, making it ideal for terminal sterilization. Thus, γ‐irradiation has been studied extensively in both the food1, 5, 6, 13–15 and medical1, 3, 9, 16–27 industries. Irradiation leaves no toxic byproducts,3, 4 making it an attractive alternative to ethylene oxide, a carcinogen which may be retained by implant materials if processing measures to remove it are inadqequate 4, 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation within the gamma frequency range (> 3*10 19 Hz) penetrates packaging materials, and can be easily applied on a large scale at ambient temperatures, making it ideal for terminal sterilization. Thus, γ‐irradiation has been studied extensively in both the food1, 5, 6, 13–15 and medical1, 3, 9, 16–27 industries. Irradiation leaves no toxic byproducts,3, 4 making it an attractive alternative to ethylene oxide, a carcinogen which may be retained by implant materials if processing measures to remove it are inadqequate 4, 10…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of 0.5 kGy irradiated myoglobin15 and ovalbumin27 has been shown using SDS‐page analysis. Tyan and colleagues noted that adhesion of platelets and red blood cells to surface‐immobilized collagen was altered as a result of 5 kGy γ‐irradiation 21. γ‐Irradiation also significantly alters the mechanical properties of synthetic biomaterials like PLGA8 and PLLA,22 natural biomaterials like gelatin23 and collagen25 and physiological tissues like bone 24…”
Section: Introductionmentioning
confidence: 99%
“…Many commercial sources of COL1 have been effectively sterilized by gamma-irradiation. Unfortunately, this practice greatly reduces its ability to form gels due to protein fragmentation and denaturation 9,10 . This procedure represents the optimal conditions for COL1 extraction as determined from many experiments performed to establish the ideal proportion of dermal sample to buffer volume.…”
Section: Discussionmentioning
confidence: 99%
“…Tyan et al [30] investigated the effect of gamma-ray irradiation (from 5 to 40 kGy) on immobilized collagen and concluded that scission of the peptide linkage occurred. They attributed the increase in amide nitrogen and the detection of carbonyl groups in irradiated collagen to the breaking of -C-nbonds according to the reaction (12.7)…”
Section: Collagenmentioning
confidence: 99%